2018
DOI: 10.1002/ppul.23942
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and atopic dermatitis after early‐, late‐, and post‐term birth

Abstract: Early-term birth was a predictor of asthma, and PT birth was associated with atopic dermatitis. Counseling against smoking and following strict indications for planned ET deliveries and cesarean sections may be means to reduce the risk of later asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
(92 reference statements)
0
17
0
1
Order By: Relevance
“…In our study, there was an association between reported asthma/asthma like symptoms and increased gestational age at delivery, but not for other factors such as mode of delivery, child's use of antibiotic medication in the past year of child's stay at the neonatal intensive care unit after birth. While early-term birth is a predictor of asthma, late term birth has also been associated with atopic dermatitis by 7 years of age 90 . Atopic dermatitis often precedes other allergic diseases such as asthma 91 , however, given the cross sectional nature of our study, we are limited in discussing this topic.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was an association between reported asthma/asthma like symptoms and increased gestational age at delivery, but not for other factors such as mode of delivery, child's use of antibiotic medication in the past year of child's stay at the neonatal intensive care unit after birth. While early-term birth is a predictor of asthma, late term birth has also been associated with atopic dermatitis by 7 years of age 90 . Atopic dermatitis often precedes other allergic diseases such as asthma 91 , however, given the cross sectional nature of our study, we are limited in discussing this topic.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 A few recent studies have suggested that early-term birth is associated with later respiratory morbidity such as asthma, 4,7,8 whereas post-term birth may decrease the risk of asthma. [9][10][11] Less information is available on the long-term respiratory infectious morbidity of children born early-term and post-term. Lower respiratory tract infections (LRTIs) are the leading cause of hospitalisation in preschool children and result in a remarkable burden on health services.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Post‐term birth has also been associated with an increased risk of adverse neonatal outcomes compared with full‐term birth . A few recent studies have suggested that early‐term birth is associated with later respiratory morbidity such as asthma, whereas post‐term birth may decrease the risk of asthma . Less information is available on the long‐term respiratory infectious morbidity of children born early‐term and post‐term.…”
Section: Introductionmentioning
confidence: 99%
“…Gestational age is associated with asthma especially in preterm infants; Korhonen et al investigated this association in over 960,000 infants focusing on exposures in the post‐term period. They found the most important risk factors for asthma at 7 years age were male sex, atopic dermatitis, intrauterine tobacco smoke exposure, early term birth, and elective cesarean section.…”
Section: Introductionmentioning
confidence: 99%